Pengaruh Pemahaman Pajak, Kesadaran Wajib Pajak, Sanksi Pajak, dan Rencana Penggunaan E-Samsat New Sakpole Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Andrawina, Widhaninggar; Mustafa, Rasyid Mei; Hasanah, Uswatun (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
This study aims to analyze the effect of tax understanding, taxpayer awareness, tax sanctions and plans for using E-SAMSAT NEW SAKPOLE on vehicle taxpayer compliance in Banyumas Regency. The type of this study is quantitative. The data used in this study is primary data. Data was collected by distributing questionnaires. The population of this study were all vehicle taxpayers in Banyumas Regency that paid their taxes in 2021. The sample of this study was 150 taxpayers. Accidental sampling was used as the sampling method. The data analysis method used was multiple linear regression analysis. Based on the data analysis results, it shows that tax understanding and tax sanctions have positive effect on vehicle taxpayer compliance. However, taxpayer awareness and plans for using E- SAMSAT NEW SAKPOLE have no effect on vehicle taxpayer compliance. The implications of this study are in order to increase vehicle taxpayers compliance in Banyumas Regency, SAMSAT of Banyumas Regency should increase taxpayers awareness so that taxpayers don’t feel forced to pay their taxes. In addition, SAMSAT of Banyumas Regency must increase the socialization about E-SAMSAT NEW SAKPOLE and improve the performance of the application so that many taxpayers use it.